PERSPEKTIF FENOMENOLOGI TERHADAP TRADISI POTANG MOGANG MANDI BALIMAU KASAI DI KELURAHAN LANGGAM, KECAMATAN LANGGAM, KABUPATEN PELALAWAN - Bunga, Bunga Edres; Jimmi Copriady; Yustina (JURNAL ILMU BUDAYA, 2024)
This research aims to determine the phenomenological perspective of the potang mogang mandi balimau kasai tradition. The benefit of this research can be as a reference or information reference in subsequent studies, to show readers a phenomenological perspective on the potang mogang mandi balimau kasai tradition. The connection between the Balimau Kasai tradition and the phenomenology of Edmund Husserl lies in the eidetic reduction view. The reality of Balimau Kasai has changed the focus and perception consumed by today's young generation has changed significantly. Therefore, from Edmund Husserl's point of view, this tradition needs to be reduced philosophically. The meaning of the Balimau Kasai tradition is seen from self-awareness of reality. Each person has a different interpretation of Balimau Kasai, depending on their experience with the tradition.